2015
DOI: 10.1177/1352458514560925
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 resistant matrix metalloproteinase-9 is the predominant serum active isoform associated with MRI activity in patients with multiple sclerosis

Abstract: Our findings suggested that the TIMP-1 resistant MMP-9 seem to be the predominantly active isoform contributing to MS disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…In light of the above considerations, we set out the present study with the aim to evaluate the contribution of MMPs, namely, active MMP-9 and MMP-2, and the cytokines/chemokines IL-17, IL-18, IL-23, and MCP-3 to the pathogenesis of MS. More importantly, for the first time we evaluated the possible intercorrelations involving these two classes of molecules. In agreement with previous studies [ 31 , 38 ], we found that serum active MMP-9 was higher in patients with MS and OND compared to healthy controls, whereas the CSF active MMP-9 was selectively elevated in MS patients. On the contrary, our finding of the lack of association between serum and CSF levels of active MMP-2 and MS disagrees with previous observations [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In light of the above considerations, we set out the present study with the aim to evaluate the contribution of MMPs, namely, active MMP-9 and MMP-2, and the cytokines/chemokines IL-17, IL-18, IL-23, and MCP-3 to the pathogenesis of MS. More importantly, for the first time we evaluated the possible intercorrelations involving these two classes of molecules. In agreement with previous studies [ 31 , 38 ], we found that serum active MMP-9 was higher in patients with MS and OND compared to healthy controls, whereas the CSF active MMP-9 was selectively elevated in MS patients. On the contrary, our finding of the lack of association between serum and CSF levels of active MMP-2 and MS disagrees with previous observations [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…C). MMP‐9, a matrix metalloproteinase associated with the opened blood brain barrier in MS, and its inhibitor, TIMP‐1, were chosen due to their validated relationship to the MS disease process . TIMP‐1 showed no statistical difference between HV and MS monocytes, but was significantly increased upon both myelin phagocytosis and pioglitazone treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, immune cells mediate both neuro-inflammation and partly axonal damage, the two main disease hallmarks leading to disease progression and increased patients' disability. Basically, MS patients exhibit an impaired Blood Brain Barrier (BBB), which indicates infiltration of leukocyte into the CNS, reflecting in increased circulating levels of active Matrix Metalloproteinases (MMPs) [109][110][111]. The same is true for pro-inflammatory cytokines, which are found to be deranged and increased both in blood and cerebrospinal fluid (CSF) of MS patients compared to controls [112,113].…”
Section: Sex Disparity In Multiple Sclerosismentioning
confidence: 99%
“…Despite the evident importance of the aforementioned biomarkers in MS physiopathology, the possible dualistic influence of sex on the MS features in relation to their levels is still largely unexplored. This is particularly evident for MMPs, for which the paucity of in vivo studies have only examined cohorts of patients without MS, despite the undisputed importance of these enzymes in the disease [110]. The few studies on MS reported an upregulation of MMP-9 in peripheral blood mononuclear cells (PBMCs) of females with the RR form [117] and a decreased expression of MMP-9 following treatment with estriol in the preclinical model of the disease [118].…”
Section: Sex Disparity In Multiple Sclerosismentioning
confidence: 99%